Optimising mathematics teaching practice in an ODeL context: A subject-specific supervisor’s perspectives - Ngoveni, Mbazima Amos; Mphahlele, Ramashego Shila; Mphuthi, Gabriel Tshepo (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2025)
Many student teachers in Open Distance e-Learning (ODeL) contexts struggle to develop strong teaching competencies, partly because supervision is often not subject-specific. This gap limits the quality of feedback needed to address discipline-related misconceptions. The study, therefore, examined how subject-specific supervision can optimise mathematics teaching practice in an ODeL environment. A qualitative, multiple-case study was conducted with five student teachers, three from Mathematics and two from Natural Sciences & Technology, participating in the Mathematics Specialist-Supervisor Pairing Programme (SSPP). Data were generated through classroom observations, lesson analysis, field notes, and reflective feedback meetings, and were thematically analysed using Pedagogical Content Knowledge (PCK) as the guiding framework. Findings showed that subject-specific supervisors were able to identify and correct key misconceptions, including misuse of brackets, misunderstanding the distributive property, misrepresenting geometric fractions, and interpreting chemical equations arithmetically. Targeted probing, modelling, and immediate feedback helped student teachers refine both content knowledge and pedagogical strategies. The study concludes that subject-specific supervision significantly enhances instructional quality in Mathematics and related STEM subjects within ODeL settings. It recommends institutionalising subject-specialist pairing models to strengthen student teachers’ PCK, improve feedback quality, and better prepare graduates for effective classroom practice.